Equifinal paths to megafauna conservation through memorable wildlife tourism experiences: evidence from the restitution of the European bison (Bison bonasus) in Poland - Akhshik, A.; Tusznio, Joanna; Strzelecka, M. (Current issues in tourism, 2023)
Despite a vast literature conceptualizing a memorable tourism experience, empirical studies overlook the context in which those experiences are produced and compiled into actions that benefit the environment. Accordingly, we need to better understand to what extent the experience of megafauna enclosures strengthens visitors' overall support for wildlife protection. To close this knowledge gap, we study memorable tourism experiences in the Bison enclosures within Poland to better understand the significance of the environmental context in which the experience induces support for protecting the species. To this end, the study employs both symmetric and asymmetric models to uncover the complexity of individual behavioural paths. The PLS-SEM results confirm the role of memorable experiences in the relationship between attitudinal and behavioural outcomes. In a complimentary manner, the fsQCA results reveal how environmental planners can analyze complex constellations of internal and external factors to elucidate the conditions that generate visitor support for wildlife protection.